Comparing the Court Mediation in Hungary and the State of Indiana in the Midwest - Schmidt, Laura; Barabás, Andrea Tünde (Magyar Rendészet, 2023)
In Hungary, court mediation has been used in criminal cases since 2007, during which it is possible for the offender and the victim of a crime to come to an agreement on their own case with the help of a facilitator and resolve their conflicts together, thus avoiding the traditional criminal justice procedure and its consequences. In the United States of America, state of Indiana, this process is called mediation, during which the parties involved can communicate with each other with the help of a third, neutral party about how they can jointly repair the harms caused by the conflict. The purpose of the article is to analyse the legal framework and practical application of court mediation in Hungary and mediation in the state of Indiana, highlighting the similarities and differences that may arise by comparing the nature of the cases, the qualifications of the mediators, and the parties taking part in the process.